Lead and cadmium content of Brazilian beers - Soares,Lucia Maria Valente (2003)
The elements called heavy metals when ingested are not completely eliminated from animal bodies and are responsible for chronic and acute intoxications. Sixty-three samples of beer, produced in the states of São Paulo, Paraná, Rio de Janeiro, Rio Grande do Sul, Minas Gerais, and Pará, were analysed for lead and cadmium content by atomic absorption spectrometry with graphite furnace atomization and Zeeman correction. The concentrations of Pb and Cd of dark differed significantly from light beers, being higher in the former. No significant difference was found between the beers produced in predominantly rural areas and the ones produced in industrialized areas. The concentrations of lead and cadmium in all samples were bellow the maximum accepted by present Brazilian regulations and ranged from not detected to 290mugPb/L and from not detected to 14.3mugCd/L. The average concentrations were 37mugPb/L and 1.6mugCd/L.